Dual-Comb Ranging - Zebin Zhu; Guanhao Wu (Engineering, 2018)
Absolute distance measurement is a fundamental technique in mobile and large-scale dimensional metrology. Dual-comb ranging is emerging as a powerful tool that exploits phase resolution and frequency accuracy for high-precision and fast-rate distance measurement. Using two coherent frequency combs, dual-comb ranging allows time and phase response to be measured rapidly. It breaks through the limitations related to the responsive bandwidth, ambiguity range, and dynamic measurement characteristics of conventional ranging tools. This review introduces dual-comb ranging and summarizes the key techniques for realizing this ranging tool. As optical frequency comb technology progresses, dual-comb ranging shows promise for various professional applications. Keywords: Ranging, Dual-comb interferometer, Phase noise, Timing jitter, Tight-locking, Post-correction